A produção para autoconsumo: características e importância para os sistemas de produção de pecuária familiar da fronteira oeste do RS - Fontoura, Andréia Furtado da (2012)
The main objective of this work is to study the production systems of familiar livestock, analyzing which are the differences in the importance of the production for self-consumption and of the food produced by the families investigated. It is understood as self-consumption all the food (with vegetal or animal origin) produced and consumed by the families or yet, those food transformed by family agro-industry. This research has as basis methodological elements of the Analysis and Diagnosis of Agrarian Systems method (ADAS) which uses some principles of the systemic approach. The references for the analysis are the production systems of familiar livestock in Manoel Viana RS, that is, the production systems which present the beef or sheep cattle and the basis of familiar labor. The social, productive and economical aspects of the familiar livestock producers were studied, as well as how the production for self-consumption happens in these families. The logics of this group of producers is different and presents a great concern with the reproduction of the family, which in many cases, is more important than the productivity and economical profits. It is possible to notice differences of importance of the production for self-consumption among the families interviewed. The main differences in the production for self-consumption among the families researched are due to external revenues (pensions mainly) and health problems of the interviewed people which prevent them from working harder. The importance of the production for selfconsumption, specially the beef, allows the families to stand long periods (sometimes two years) without selling their production, because their monthly needs are financed by other revenues (pensions in many cases). And being the beef a product which is present every day in the meals and which has a high commercial value, the expenditures with alimentation decrease a lot and are reduced even more because of the production of other foods (other products of animal origin, subsistence farming, orchards, vegetable gardens and familiar agro-industry). If the value of the production for self-consumption is considered as revenue, it is observed that the familiar farms present high profits, because if they didn t produce anything, a significant amount of financial resources should be spent to buy products for alimentation.